Electrical and structural properties of Ti/Au ohmic contacts to n-ZnO - Kim, HK; Han, SH; Seong, TY; Choi, WK (ELECTROCHEMICAL SOC INC, 2001)
We have investigated Ti/Au (30/50 nm) ohmic contacts to n-ZnO:Al. The samples are annealed at temperatures of 300 and 500 degreesC for 60 s in a flowing N-2 atmosphere. Current-voltage measurements show that the as-deposited sample is ohmic with a specific contact resistance of 2 X 10(-2) Omega cm(2). However, annealing of the sample at 300 degreesC results in much better ohmic behavior with a contact resistance of 2 X 10(-4) Omega cm(2). Further increase in annealing temperature (500 degreesC) causes the degradation of the ohmic property. Glancing angle X-ray diffraction and Auger electron spectroscopy are used to investigate interfacial reactions between the Ti/Au and ZnO layers. It is shown that both rutile and srilankite TiO2 phases are formed in the as-deposited and annealed samples. It is further shown that annealing at 500 degreesC results in the formation of new phases such as Ti3Au and TiAu2. A possible explanation is given to describe the annealing temperature dependence of the specific contact resistance. (C) 2001 The Electrochemical Society. All rights reserved.
Keywords: FILMS